Effects of Project-Based Learning Model and Cooperative Learning Model in Improving Student Social Skills in Physical Education - Dicky Tri Juniar; Adang Suherman; Beltasar Tarigan; Agus Mahendra (Universitas Pendidikan Indonesia, 2023)
Learning models in the 21st century are started to be widely used to develop students’ social skills in dealing with various problems. In reality, many students still have not been able to solve social problems. It becomes an ambiguity as the learning models are assumed to be influential in overcoming the problems through meaningful learning. Project-based and Cooperative Learning Models are learning models that are assumed to be effective in developing social skills. However, these two learning models have not received consistent conclusions because previous studies have not specifically compared the two models, especially in Physical Education. This study aimed to determine the effect and prove the effectiveness of project-based and cooperative learning models on student social skills in Physical Education, especially for Senior High School students. The implementation of this research used experimental methods with real experimental designs. Researchers selected two classes at a high school in Tasikmalaya City, West Java, Indonesia, using cluster sampling. The data collection instrument employed a 3-point scale questionnaire (